Development Of Nutrisportextm-Interactive Sport Nutrition Based Mobile Application Software - Mohd Razif, Shahril; B. S., Pushpa; N. S., Safii; C. L., Ming (2018)
NutriSportEx™ mobile application was developed for both Android and iOS platforms, as an open source and on Linux-based operating system for mobile devices such as smartphones. It calculates total energy requirement based on user’s weight. It offers users the ability to plan and record their meals from a food database and provides nutritional information of the selected food. NutriSportExTM tabulates dietary intake and generates a nutritional analysis report in the form of infographics. The nutritional report covers details such as total calorie intake and macro-and micro-nutrients intake.The food excel feature which is an education module provides additional information such as dietary guidelines, micronutrients, macronutrients, food guide pyramid and food planning with sample meal set for 2400 and 3200 kcal. NutriSportExTM mobile application has great potential to be well accepted